Impact of Covid-19 Pandemic on Tourists' Behavior and Preferences: A Critical Insight - Khan, Mohd Asif; Khan, Shahzar Ali; Khan, Verda (South Asian Journal of Social Sciences and Humanities, 2022)
Purpose: This paper aims to explore the variations in tourists' behavior and preferences due  to the COVID-19 pandemic and highlight the latest tourism and hospitality industry trends. Design/methodology/approach: This paper is based on a review of the allied literature on  tourist preferences, tourist behavior, tourism marketing, tourism management, and a  combination of reports from various organizations.  Findings: The paper identifies that the COVID-19 pandemic has significantly impacted the  tourists' behavior and preferences regarding their choice of accommodation, transportation, and destination, which has increased the popularity of domestic tourism, sustainable travel,  free and independent travel, and short-distance trips. COVID-19 has accelerated the trend of  safety and hygiene, virtual reality, cashless payment, contactless services, travel bubbles, and  artificial intelligence and robots. There is a significant possibility that these trends will  continue. Practical implications: It is essential to adopt the latest tourism and hospitality trends in  response to tourists' changing behavior and preferences due to the COVID-19 pandemic. Keeping  up with the latest trends in the industry will give the best opportunity to reach the target audience  and ensure that the business delivers the customer experience that consumers want and expect. Originality: This paper provides a comprehensive overview of how COVID-19 has impacted  tourists' behavior and preferences. This is the first study to highlight the latest tourism and  hospitality industry trends during and after the pandemic.
Keywords: COVID-19; Tourists' preferences; Travel behavior; Latest trends